Pendampingan Implementasi Pembelajaran Guided Discovery Melalui Lesson Study for Learning Community (LSLC) untuk Peningkatan Kemampuan Berpikir Kritis Kimia Siswa SMA Zonasi Narmada Kabupaten Lombok Barat - Muntari Muntari; Muti’ah Muti’ah; Syarifa Wahidah Al Idrus; Supriadi Supriadi (Jurnal Pengabdian Magister Pendidikan IPA, 2021)
The implementation of the learning process is always oriented towards the mastery of competence by students. One of the important competencies possessed by students is high order thinking skills (HOTS). Based on the results of observations in several high schools in the Narmada zoning, West Lombok district, it was obtained: (1) The ability of student’s critical thinking in chemistry on average was still low; (2) Students do not have the opportunity to develop the potential for critical thinking skills in learning due to the use of unsuitable learning models; (3) The ability of teachers to apply learning models that can improve students' critical thinking skills is still low; and (4) Teachers carry out learning individually so that it is difficult to evaluate the learning process as a result of continuous improvement of learning difficult to implement. The solution offered in this community service activity is in the form of teacher assistance in implementing zoning-based of lesson study for learning communities (LSLC) to improve students' critical thinking skills in chemistry. The targets of this community service activity are teachers of chemistry subjects from SMA Negeri 1 Narmada, SMA Negeri 2 Narmada, SMA Negeri 1 Lingsar, and SMA NW Narmada. This activity was carried out with a training approach, learning practice, and reflection. This activity was carried out in two stages: the first stage is socialization and workshop about LSLC, then in the second stage the lesson study (LS) practice. The results achieved from this activity are: (1) Students' critical thinking skills in chemistry subjects need to be continuously improved through various learning innovations, one of which is by implementing guided discovery learning; (2) Increased understanding of teachers regarding the principles, benefits, and scope of the lesson study and LSLC appropriately; and (3) The increased enthusiasm of teachers to implement lesson study-based learning improvements which consist of planning stages (plan), implementation of learning and observation (do), and reflection (see), and re-design.